Management of natural disasters in the environment PT. Mutiara Masyhur Sejahtera with the formation of an emergency response team - Amukti, Bintang; Efendi, Mohamad Fran; Ahsanuddin, Cundik; Budi, Andyka Setyo; Nareswara, Kharisma (Journal of Economic, Business & Accounting Research, 2024)
Background: Sidoarjo Regency, East Java, is often hit by tornadoes that cause material losses and injuries, especially at PT. Mutiara Masyhur Sejahtera located in Sidoarjo. This phenomenon encourages the need to improve disaster preparedness and response. Method: This study uses a qualitative descriptive approach with primary data collection through direct observation and in-depth interviews with the company's Project Manager. Secondary data covering organizational structure and number of employees are also used. Data is analyzed through a reduction process to ensure relevant and accurate information. Findings: Although PT. Mutiara Masyhur Sejahtera already has fire protection equipment, such as Light Fire Extinguishers, but there is no system or policy that regulates emergency response management for fires or other disasters. Forming an Emergency Response Team and creating Procedures and Work Instructions (IKA) regarding Emergency Response are needed as a reference when an emergency occurs. Conclusion: To improve disaster preparedness, companies must equip themselves with an occupational safety and health management system that regulates all compliance related to K3 aspects. This aims to prevent work accidents and occupational diseases, reduce the negative impact of disasters and improve overall work safety. Novelty/Originality of this study: This study presents a new approach to improving disaster preparedness in the private sector, especially for companies operating in disaster-prone areas such as Sidoarjo. This study proposes the integration of an occupational safety and health management system (OHSMS) with a particular focus on disaster emergency response management, which can be a model for other companies in improving disaster resilience.